To Compare Early Outcomes of Warm Verses Cold Blood Cardioplegia in Patients Undergoing Elective Coronary Artery Bypass Graft Surgery (CABG) - Goher Bashir, Ajwad Farogh, Muhammad Irfan Khan, Asma Hassan, Naseem Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To compare the effects of warm versus cold blood cardioplegia on the myocardium of patients undergoing elective Coronary Artery Bypass Graft (CABG) surgery. Study Design: The study was the Prospective Observational study. Place and Duration of Study: At the Punjab Institute of Cardiology in Bahawalpur, Pakistan, 100 patients with ischemic heart disease was scheduled for open-heart surgery. Methodology: From the 25th of October 2021 to the 25th of October 2022, this prospective observational study was carried out in the Cardiac surgery Department of the PIC in Bahawalpur. One hundred patients participated in this research project overall. The means and standard deviations of the continuous variables were reported, while the frequencies of the categorical variables were given in percentage. SPSS 24 version was utilized for the statistical analysis. The All P values <0.05 were considered statistically significant Results: Our results showed that out of 100 patients the mean age of the cases in Group-A was 57.12±3.9 and in Group-B was 55.45±2.6 with insignificant p-value. The findings of current study showed that the male 41(82.0%) and female 9(18.0%) patients in Group-A while male 38(76.0%) and female 12(24.0%) in Group-B with p-value 0.659. Clinical characteristics i.e. The hypertensive 39(78.0%) in Group A while 35(70.0%) in Group B with significant p-value 0.017. Similarly hyperlipdemia in Group A as 11(22.0%) compared with 15(30.0%) with 0.069. Renal failure patients in Group A was 4(08.0%) while in Group B 3(06.0%) observed with p-value 0.032. The clinical characteristics i.e. (CPB time, cross clamp time, cardioplegia dose, number of grafts and complete revascularization) were statistically significantly as p-value < 0.05. Conclusion: According to the available data, the surgeon can make the call between warm and cold cardioplegia when it comes to patient safety. Keywords: CK-MB, CPB, CABG.